Platform Digital Kelurahan Babau - Paskalis Andrianus Nani; Patrisius Batarius; Natalia Magdalena Rafu Mamulak; Paulina Aliandu; Emerensiana Ngaga; Sisilia Daeng Bakka Mau; Yovinia Carmeneja Hoar Siki; Frengky Tedy; Alfry Aristo J. SinlaE; Ign. Pricher A. N. Samane; Donatus J. Manehat; Adri Gabriel Sooai (Patria : Jurnal Pengabdian Kepada Masyarakat, 2020)
Managing letters related to residence in Babau Village usually takes a long time. Residents must meet directly with the head of the RT/RW in the domicile area to obtain a cover letter, then they can go to the Kelurahan office to arrange the intended documents. The problem that then arises is if the community cannot meet the RT/RW leader because of busy life. Likewise if it arrives at the Kelurahan office, it turns out that the Lurah is not there. This will certainly hinder the management process. In addition to the above problems, another problem that can also arise is the RT/RW cover letter that has the potential to be falsified.These problems can be solved by building a Digital Village platform where the community does not need to meet directly with the RT/RW but can use the existing platform to manage the required documents. The proposal letter that goes to RT/RW can be directly approved and forwarded to the Village Head to be approved and ready to be printed. Everything is done without the need for paperless paperwork.